Asymmetric Color‐Changeable Luminophore with Donor–Acceptor–Donor Structure for Solvent and Temperature Sensitive Properties. Issue 39 (22nd October 2018) - Kitagawa, Yuichi; Yachi, Ryuto; Nakanishi, Takayuki; Fushimi, Koji; Hasegawa, Yasuchika
Abstract: An asymmetric donor–acceptor–donor (D–A–D) type organic luminophore is reported for solvent and temperature sensors. The electronic absorption and luminescence properties of the luminophore were assessed from its electronic absorption and luminescence spectra, which depended on the external environment. The D–A–D luminophore showed environment‐sensitive charge transfer fluorescence based on structural transformation through excited singlet states. Characteristic D–A–D phosphorescence was also observed at 494 nm, which was shorter than that of the D–A–D fluorescence (502 nm). In this study, the novel photophysical properties of a D–A–D‐type luminophore induced by its asymmetric electronic structure are described. Abstract : We have designed and synthesized a novel asymmetric donor–acceptor–donor‐type organic luminophore. The luminophore exhibited solvent‐ and temperature‐sensitive fluorescence derived from two stable fluorescent structures in singlet states. A blue‐shifted phosphorescence band relative to the fluorescence band was also observed. An asymmetric D–A–D luminophore based on our conceptual design opens new possibilities in photochemistry, analytical chemistry and organic material chemistry.